Evaluation of Sewing Skills Program at Zere – Amin Course and Training Institute (LKP) - Amin, Elvira Dwi Rahayu; Sumarno, Sumarno; Matondang, Zulkifli (Jurnal Riset Ilmu Pendidikan, 2025)
Evaluation of the sewing skills training program at the Zere AMIN Course and Training Institute (LKP) aims to assess the effectiveness of program implementation using the CIPP (Context, Input, Process, Product) evaluation model. This study uses a descriptive evaluative approach with mixed methods, namely qualitative and quantitative. The subjects of the study consisted of instructors and training participants, with data collection techniques in the form of questionnaires, observations, interviews, and documentation. The evaluation results show that this program is classified as very adequate in all evaluation components. The program is considered relevant to the needs of participants (Context), has adequate facilities, curriculum, and instructors (Input), implements an effective learning process (Process), and is able to improve participants' sewing skills and encourage them to be economically independent (Product). These findings indicate that the sewing training program at LKP Zere AMIN has succeeded in achieving its learning objectives and has a positive impact on community economic empowerment.